Hierocracia e inovação, dinâmica do conceito na Sociologia da Dominação - Luciano Sathler (Ciências Sociais Unisinos)
This paper aims to compare the use of the concept of hierocracy, in its dynamic complexity, in various historical roles it assumes, especially in terms of its influence on the development of Western modernity. The main text used for this analysis is Sociology of Domination, by Max Weber. The article discusses the relationship of hierocracy with political power, petty bourgeoisie, bourgeoisie, capitalism, democracy and human rights. It makes some considerations about hierocracy as fundamental to the development of Weber’s sociology, as a necessary step to understand what is rationality, modernity, disenchantment of the world and heroic individualism, which are essential elements of the author’s theoretical constructs.